Pengaruh Viral Marketing dan Harga Terhadap Keputusan Pembelian Produk Melalui Shopee Live pada Mahasiswa Prodi Pendidikan Ekonomi Universitas Pendidikan Ganesha - Ni Nyoman Ari Widiasih; Sujana, I Nyoman (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
This research aims to find out the influence of viral marketing and price on how purchasing decisions through Shopee Live on students of Study Program  Education Economics of Ganesha University of Education. This research is a kind of quantitative causal research. The population of this study was students of the economic education study program 1.3,5 and 7 semesters with a total of 328 students. Purposive sampling is a sample-taking technique with a total of 180 students. The method of gathering data in this study is by spreading the questionnaire. This research involves a double linear regression analysis, but the results of this study show that: (1) there is a positive and significant influence of viral marketing on purchasing decisions, (2) prices have a significant and positive influence on purchase decisions, and (3) simultaneously viral Marketing and prices also have a positive, significant impact on buying decisions.